Current modeling approaches to experimental cognitive impairment (a literature review) - D. V. Tymofiiv; O. V. Hancheva (Zaporozhye State Medical University, 2022)
The aim of the work is to review the professional literature sources from the scientific database PubMed mainly for the last 20 years analyzing the modern view on approaches to experimental modeling of cognitive impairment. Materials and methods. A review of the scientific literature over the past 20 years was performed. The lack of requisite knowledge about the pathogenesis of cognitive impairment and the wide range of risk factors for these conditions continue to be major challenges in the development of guidelines on early diagnosis and treatment. The literary analysis suggests that all modeling approaches to experimental cognitive impairment are currently divided into two groups: cell culture and animal models. Conclusions. Experimental modeling of cognitive impairment remains important in addition to clinical and population-based studies. In recent years, the problem of selecting an adequate model to study cognitive impairment, which is a central clinical manifestation of various neurological diseases (Alzheimer's and Parkinson's diseases, traumatic brain injury, vascular, demyelinating, and infectious diseases, metabolic aberrations and hormonal imbalance, neurodegenerative diseases of the central nervous system) is becoming increasingly relevant. The choice of model and experimental material - animals or cultures (invertebrate and mammalian cells) is based on a clear understanding of the study design and depends on the ultimate goal of research.